2018
DOI: 10.3393/ac.2018.34.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Affecting the Clinical Course of Patients With Diverticulitis: Who Needs Hospital Management?

Abstract: PurposeThe aim of this study is to determine the predictable factors that affect the clinical course, especially the hospital stay, the operation performed, and to determine factors that will be helpful in deciding whether in-hospital or outpatient treatment is appropriate.MethodsWe retrospectively collected medical data for patients who had been diagnosed with acute diverticulitis at Inje University Sanggye Paik Hospital between January and December 2016. In total, 117 patients were enrolled in this study. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…This review showed that the localization of diverticulitis in the sigmoid colon is not a selection criterion for outpatient management; there is no difference in failure rate between overall (3.79%) versus a selected group with left colon diverticulitis (5.38%). This result disagrees with the results of Yoo et al [32], in which the hospital stay was significantly lower in right diverticulitis (p = < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This review showed that the localization of diverticulitis in the sigmoid colon is not a selection criterion for outpatient management; there is no difference in failure rate between overall (3.79%) versus a selected group with left colon diverticulitis (5.38%). This result disagrees with the results of Yoo et al [32], in which the hospital stay was significantly lower in right diverticulitis (p = < 0.001).…”
Section: Discussioncontrasting
confidence: 99%
“…For the remaining 27 studies, the full texts were obtained and reviewed. Six studies were excluded on the basis of reasons listed in the section of characteristics of excluded studies [20,21,[30][31][32][33]. In total, 21studies fulfilled the inclusion criteria [13-19, 22, 23, 34-45], (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…118 Yoo et al showed no association between the presence of diabetes and need for surgery in their retrospective review of 117 patients with AD. 119 For these reasons comorbidity score is not considered an absolute contra-indication to the out-patient management of uncomplicated AD, but clinical judgement should be used.…”
Section: Comorbidity Scorementioning
confidence: 99%